Konsep Shiddiq dan Religiusitas dalam Manajemen Pengelolaan Pertanian Kebun Kopi Segaran di Kecamatan Tiris, Probolinggo - Al Ahsani, Nasirudin (Fakultas Dakwah UIN KHAS Jember, 2024)
This study examines the role of the concept of Shiddiq and religiosity in the management of coffee plantation agriculture in Tiris District, Probolinggo. While coffee farming practices in Indonesia generally still rely on conventional methods, this research identifies a gap in studies linking religiosity values, particularly Shiddiq, with agricultural sustainability. The aim of this study is to understand how the concept of Shiddiq is applied by coffee farmers in their agricultural practices and its impact on sustainability and social welfare. The study uses a qualitative approach with a case study method, involving in-depth interviews and observations with farmers in Segaran Village. The findings show that the value of Shiddiq supports the implementation of organic farming and sustainable natural resource management, which contributes to improved soil quality and crop yields, while also preserving the environment. This study suggests that the integration of religiosity values into agricultural management can serve as an effective model for environmentally friendly and sustainable farming practices.